Biografías olvidadas y marginalidad en la Edad Media y Moderna en la Corona d'Aragón. - RIBERA GRACIA, CARLES (Scripta)
The article presents a review of the book "Forgotten Biographies and Marginality in the Medieval and Modern Ages in the Crown of Aragon," edited by Vicent Josep Escartí and Alejandro Llinares. This work, composed of eleven chapters, explores the lives of marginalized individuals and groups in the Crown of Aragon, using an interdisciplinary approach that combines history, literature, and sociology. Through various documentary sources, the authors reconstruct life stories that have remained in the shadows, addressing topics such as prostitution, religious persecution, and social marginalization. The book stands out for its contribution to historiography, challenging traditional narratives and enriching the understanding of the past.